PENGEMBANGAN SISTEM INFORMASI PENGELOLAAN BEASISWA POLITEKNIK CALTEX RIAU - Arifin, Satria Perdana; zainal Arifin Renaldo; Surya, Ibnu (Politeknik Caltex Riau, 2025)
Politeknik Caltex Riau manages several scholarships whose funding sources can come from the government or private sector. The management of this scholarship scheme is done manually in the form of collecting files and recaps via Ms. Excel. In addition, the scholarship management process is carried out by an operator, namely the Head of Student Affairs, so it takes a long time to carry out the selection process until the announcement of scholarship recipients and has the potential for errors. The errors that occur include duplication of scholarship recipients, miscalculation of the scholarship funds submitted and inconsistency in writing data related to scholarship recipients. In fact, the presentation of information on scholarship recipients is absolutely needed as reporting material to related parties, such as reporting Scholarships to the Riau Provincial Government. Therefore, to assist the operator in managing scholarships, an information system was developed to manage Scholarships at Politeknik Caltex Riau. In the development of this information system, it was built based on software development standards, namely the Software Development Life Cycle (SDLC) with Waterfall Methodology. The scholarship management system was tested on the head of student affairs, executives and scholarship recipients. From the results of testing this information system, there were no errors and it could run well. In addition, in terms of system acceptance by users, it can be concluded that this system is acceptable and makes it easier to manage scholarships